2020
DOI: 10.1111/btp.12788
|View full text |Cite
|
Sign up to set email alerts
|

Agouti reintroduction recovers seed dispersal of a large‐seeded tropical tree

Abstract: The aim of animal reintroductions has mainly been species recovery; only few reintroduction initiatives focus on ecosystem restoration. Therefore, reintroduction consequences on ecological interactions are seldom assessed. We used the interaction between a reintroduced population of agoutis (Dasyprocta leporina) and a vulnerable tropical endemic tree (Joannesia princeps) to examine reintroduction effects on seed dispersal and seedling establishment. To test the outcomes of this interaction, we tracked seeds of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 57 publications
0
31
0
Order By: Relevance
“…Our results show they are highly original and disperse larger seeds that have fewer dispersers in the Park. A recent study has identified that one of the largest seeds in TNP ( Joanesia princeps ) only germinated when buried by agoutis (Mittelman et al 2020). Moreover, due to their scatter-hoader behaviour, agoutis are able to disperse large seeds over great distances (Jansen et al 2012).…”
Section: Case Studymentioning
confidence: 99%
“…Our results show they are highly original and disperse larger seeds that have fewer dispersers in the Park. A recent study has identified that one of the largest seeds in TNP ( Joanesia princeps ) only germinated when buried by agoutis (Mittelman et al 2020). Moreover, due to their scatter-hoader behaviour, agoutis are able to disperse large seeds over great distances (Jansen et al 2012).…”
Section: Case Studymentioning
confidence: 99%
“…"Functional rescue" implies that an ecological process has been lost through local extinction, but that it can be recovered through species reintroduction or ecological replacement. For example, translocated populations of frugivores such as tortoises (Griffiths et al, 2011) and agouti (Mittelman et al, 2020) have reversed the suppressed recruitment of rare tree species in their respective habitats. In defaunated ecosystems, ecological functions such as seed dispersal may be dependent on remnant animal populations.…”
Section: Introductionmentioning
confidence: 99%
“…This rodent has been identified as a selective group of animal that has the potential to be domesticated [ 3 ], and some authors have also grouped them as mini-livestock [ 4 ]. This rodent is essential as a seed disperser and plays a crucial role in reforestation [ 5 ]. This rodent also has a wide range of habitats from savannahs to rainforests [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%